Describing heterogeneity of unmet needs among adults with a developmental disability: An examination of the 2012 Canadian Survey on Disability. (June 2017) - Zwicker, Jennifer; Zaresani, Arezou; Emery, J.C. Herb
Highlights: Experiences reported by persons with DD from Canadian population data. Labour force participation is a greater challenge for persons with DD than other disabilities. Heterogeneity in unmet workplace and education needs depending on type of disability. Supports with activities of daily living is needed by almost all persons with DD. A lifespan perspective is needed when considering design of employment-related policy. Abstract: Background: As a signatory to the UN Convention on the Rights of Persons with Disabilities, Canada has committed to protect the rights and dignity of persons with developmental disabilities (DD), which means that labour markets, education, and training opportunities should be inclusive and accessible. Purpose: Describe the unmet employment, education and daily needs of adults with DD, with a sub analysis of persons with autism spectrum disorder (ASD) and cerebral palsy (CP) in Canada, to inform efficient and equitable policy development. Methods and procedures: Secondary analysis of 2012 Canadian Survey on Disability was used to study a sample including working age (15–64 years old) individuals with self-reported DD, CP and ASD. Persons with DD reported on their met and unmet needs in term of activities of daily living, education and employment. Outcomes and results: Labour force participation is the lowest for those with DD compared to any other disability. Individuals with CP and ASD report a high level of unmet needs that differ in terms of educational, vocational and daily living supports. Conclusions and implications: Improving labour force participation to be inclusive and accessible requires policy that considers the range of unmet needs that exist for persons with DD.